2019
DOI: 10.2147/clep.s191418
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology of systemic sclerosis and systemic sclerosis-associated interstitial lung disease</p>

Abstract: Background: Interstitial lung disease (ILD) is one of the leading causes of mortality in patients with systemic sclerosis (SSc). To further understand this patient population, we present the first systematic review on the epidemiology of SSc and SSc-associated ILD (SSc-ILD). Methods: Bibliographic databases and web sources were searched for studies including patients with SSc and SSc-ILD in Europe and North America (United States and Canada). The systematic review was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 61 publications
13
125
4
3
Order By: Relevance
“…Our results for the incidence of ILD according to subtypes were similar. Our study had similar results to European, North American, and other studies done in Thailand that found that SSc is found mostly in females 8,10,11 . Pulmonary involvement was related to specific ethic, socioeconomic, and behavioral factors in SSc 15 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results for the incidence of ILD according to subtypes were similar. Our study had similar results to European, North American, and other studies done in Thailand that found that SSc is found mostly in females 8,10,11 . Pulmonary involvement was related to specific ethic, socioeconomic, and behavioral factors in SSc 15 .…”
Section: Discussionsupporting
confidence: 91%
“…The pathogenesis of SSc-ILD remains unclear; however, three steps of pathogenesis have been proposed: (1) persistent and repeated injuries of endothelial cells; (2) activation of innate/adaptive immunity; and (3) fibroblast recruitment/activation 4 . From previous studies, the associated factors of lung function decline in SSc-ILD are black males, diffuse type, and presence of antinuclear antibodies, anti-topoisomerase I, and anti-Th/To, but the absence of anti-centromere antibodies [4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is frequent in systemic sclerosis (SSc), with a prevalence reported between 35 and 52% [1]. Considering that ILD represents a major cause of mortality in SSc [2], preventing the progression of respiratory impairment is of utmost importance to improve life expectancy of SSc patients and it has been the target of several investigational studies.…”
Section: Introductionmentioning
confidence: 99%
“…ILD is one of the leading causes of morbidity and mortality in SSc [9,104,137]. SSc-ILD has an estimated prevalence of 1.7-4.2 per 100,000 individuals in Europe [138]. The SENSCIS trial investigated the use of nintedanib in patients with SSc-ILD.…”
Section: Other Progressive Fibrosing Ildsmentioning
confidence: 99%